Analysis of Shape-Memory-Alloy Fiber Interface Strength for Optimization of Self-Healing Composites - Haider, Muhammad Istiaque; Salowitz, Nathan P (Proceedings of the Wisconsin Space Conference, 2023)
Self-healing materials, possessing an innate ability to mend damage and restore structural strength, have tremendous potential to improve safety and reliability, especially in space applications where recovery or manual performance of repairs may be prohibitive, dangerous, or impossible. Self-healing metallic materials developed with Nickel Titanium (NiTi) Shape Memory Alloy (SMA) reinforcement showed a promising prospect for recovering from larger scale damage. However, NiTi is known to form an inert oxide (TiO2) surface layer that is extremely hard to attach to. In this research, to promote better strength between the fiber and matrix, TiO2 surface layer has been removed by etching the NiTi wires in an inert environment and a pull test has been performed to evaluate the resulting change in adhesion strength between the fiber and metallic matrix. The experimental investigation of these interface fracture scenarios will enable the efficient design of composite materials.